2000
DOI: 10.1200/jco.2000.18.4.780
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor After Intensive Consolidation Chemotherapy in Acute Myeloid Leukemia: Results of a Randomized Trial of the Groupe Ouest-Est Leucémies Aigues Myeloblastiques

Abstract: G-CSF should be administered routinely after ICC to reduce the duration of neutropenia and hospitalization. However, G-CSF did not seem to significantly increase the feasibility of this two-course program or modify overall outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 25 publications
0
68
2
2
Order By: Relevance
“…Patients with severe neutropenia (Ͻ100 granulocytes/ mm 3 ) are at greatest risk (9,10), and the mortality rate for patients developing pneumonia in this setting can be as high as 67% (4). With the advent of stem cell transplantation and the use of colonystimulating factors, the duration of neutropenia post-BMT has been significantly shortened (11)(12)(13)(14)(15). Despite this, immunodeficiency can persist, and patients remain at increased risk for pulmonary infections.…”
Section: Defective Phagocytosis and Clearance Of Pseudomonas Aeruginomentioning
confidence: 99%
“…Patients with severe neutropenia (Ͻ100 granulocytes/ mm 3 ) are at greatest risk (9,10), and the mortality rate for patients developing pneumonia in this setting can be as high as 67% (4). With the advent of stem cell transplantation and the use of colonystimulating factors, the duration of neutropenia post-BMT has been significantly shortened (11)(12)(13)(14)(15). Despite this, immunodeficiency can persist, and patients remain at increased risk for pulmonary infections.…”
Section: Defective Phagocytosis and Clearance Of Pseudomonas Aeruginomentioning
confidence: 99%
“…Consequently, randomized trials have analyzed whether the use of myeloid growth factors can reduce the duration of chemotherapyinduced neutropenia in AML patients without compromising antileukemic treatment. However, no consistent detrimental effects on survival have been reported with myeloid growth factors given to promote hematologic recovery following induction chemotherapy or after consolidation chemotherapy [10][11][12][13]. In contrast, the use of myeloid growth factors in AML patients to enhance hematologic recovery after HDCT with ASCT has not been similarly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, shortening the duration of neutropenia with granulocytecolony stimulating factor (G-CSF) after ASCT is expected to reduce infectious complications [9]. In fact, G-CSF given to support hematologic recovery following induction chemotherapy in AML patients has been shown to reduce the duration of neutropenia, the number of febrile episodes, the duration of hospitalization and the requirement for parenteral antibiotics [10][11][12][13]. In contrast, it is of no benefit if given together with chemotherapy as a priming strategy to improve survival rates [14].…”
Section: Introductionmentioning
confidence: 99%
“…G-CSF therapy has considerably improved the safety of myelosuppressive chemotherapy, most notably in patients with lymphoma, and a decrease in the treatment-related mortality, higher complete remission rates, and longer diseasefree survival times have been reported in these patients (16,17,37). In addition to shortening the duration of neutropenia and hospitalization, G-CSF reduces the incidence of infections in patients with lymphoma (18,26,28,34). Although G-CSF generally has few side effects, some studies have indicated that G-CSF can exacerbate the lung toxicity caused by pneumotoxic agents (4,19,32) and can cause harmful lung effects even in the absence of known pneumotoxic drugs (4).…”
Section: Introductionmentioning
confidence: 99%